Being dishonest to feel better: How intolerance of uncertainty fuels performance misreporting - Khajehnejad, Sabra; Kumar, Amit; Sinaceur, Marwan (Accounting, Organizations and Society, 2026)
This paper proposes that individuals with higher intolerance of uncertainty are more prone to misreporting their performance in internal reporting settings when there is high performance evaluation uncertainty. In contrast, under low performance evaluation uncertainty, intolerance of uncertainty does not affect performance misreporting. We test this prediction across six studies. Studies 1–4 operationalize performance evaluation uncertainty through supervisor's word-deed inconsistency and examine the effect in real-world (Studies 1–2) and controlled experimental settings (Studies 3–4). To assess generalizability, Study 5 manipulates leadership and organizational change and Study 6 manipulates market change to create different levels of performance evaluation uncertainty. Across all six studies, we find consistent support for our hypothesis. Individuals with higher intolerance of uncertainty experience stronger uneasy, negative feelings (e.g., discomfort and anxiety) when performance evaluation uncertainty is high, and the desire to reduce these negative feelings leads them to impulsively misreport their performance. This paper highlights the emotion-driven aspect of performance misreporting and demonstrates that misreporting is shaped not only by individual traits but also by supervisor's behavior and broader organizational and environmental factors that contribute to performance evaluation uncertainty.